2008
DOI: 10.1002/qua.21643
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory calculation of 2p spectra of SiH4, PH3, H2S, HCl, and Ar

Abstract: ABSTRACT:The method developed recently for prediction of 1s electron spectra is now extended to the 2p spectra of SiH 4 , PH 3 , H 2 S, HCl, and Ar. The method for X-ray absorption spectra involves the use of ⌬E for the excitation and ionization energies, and application of timedependent density functional theory using the exchange-correlation potential known as statistical average of orbital potentials for the intensities. Additional assumptions and approximations are also made. The best exchange-correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
3
1
1
Order By: Relevance
“…46 In terms of relative intensities, it is to be noted that the lowest a 1 peak, corresponding to excitations from 2p 3/2 , is significantly less intense than the second peak due to transitions from 2p 1/2 , and it is clearly not possible to rely on a statistical distribution of intensity. 53 This counterintuitive trend, deviating from the 2 : 1 statistical ratio of electron population of subshells, is observed for all silane derivatives in the present study. Such non-statistical intensity ratios have been observed for numerous systems, and these have been attributed to a sensitive balance between core-hole spin-orbit and electron-hole exchange interactions 7,17,25,42,44 -in the independent-particle approximation only core-hole spin-orbit interactions would be in effect, and the ratio would thus be 2 : 1.…”
Section: Resultscontrasting
confidence: 70%
See 1 more Smart Citation
“…46 In terms of relative intensities, it is to be noted that the lowest a 1 peak, corresponding to excitations from 2p 3/2 , is significantly less intense than the second peak due to transitions from 2p 1/2 , and it is clearly not possible to rely on a statistical distribution of intensity. 53 This counterintuitive trend, deviating from the 2 : 1 statistical ratio of electron population of subshells, is observed for all silane derivatives in the present study. Such non-statistical intensity ratios have been observed for numerous systems, and these have been attributed to a sensitive balance between core-hole spin-orbit and electron-hole exchange interactions 7,17,25,42,44 -in the independent-particle approximation only core-hole spin-orbit interactions would be in effect, and the ratio would thus be 2 : 1.…”
Section: Resultscontrasting
confidence: 70%
“…The experimental spectra of these molecules are well investigated, especially for the L 2,3 -edges [37][38][39][40][41][42][43][44][45][46][47][48][49] where vibrationally resolved spectra are available, 45,46,48,49 but a number of experimental studies on the L 1 -edge [38][39][40][41][42][43] and the K-edge 50,51 are also found in the literature. From a theoretical standpoint, X-ray absorption spectra have traditionally been interpreted using variations of the Xa method and configuration interaction, 37,51,52 but more recent TDDFT results for SiH 4 53 and SiF 4 54 are also available.…”
Section: Introductionmentioning
confidence: 99%
“…The 2s and 2p core level electron spectra of the third-period elements were studied experimentally by X-ray absorption spectroscopy (XAS) and X-ray photoelectron spectroscopy (XPS). Theoretically, Chong et al calculated 2p spectra of SiH 4 , PH 3 , H 2 S, HCl, and Ar by KS density functional theory (DFT). Their calculated XAP for 2p ionization is generally in good agreement with the experiment.…”
Section: Introductionmentioning
confidence: 99%
“…The 2s and 2p core level electron spectra of the third-period elements were studied 25 experimentally by X-ray absorption spectroscopy (XAS) and X-ray photoelectron spectroscopy (XPS). Theoretically, Chong et al 41 In previous studies, 36,37 we studied the 1s core ionization energies of second-and third-period elements by using HF and KS SCF theory. We used ΔSCF, STS, and two corrected STS methods [termed shifted STS (1) and shifted STS (2), to accurately reproduce ΔSCF and the experiment, respectively].…”
Section: Introductionmentioning
confidence: 99%
“…O método apresenta resultados excelentes, que diferem dos valores experimentais por menos de 0,2 eV. [43][44][45][46][47][48] Além das energias de ionização de caroço, recentemente o método de Chong têm sido utilizado para determinar energias de dupla ionização de valência de uma série dé atomos e moléculas 49 , mostrando boa precisão. Entretanto, os métodos baseados na Teoria do Funcional de Densidade formalmente não são capazes de tratar estados excitados, o que pode nos direcionar a descartar de imediato o seu uso no cálculo de energias de ionização.…”
Section: Abordagem Teórica E Computacionalunclassified